Otoritas Imam Ma’shum dalam Epistemologi Hukum Syi'ah Imamiyah: Kritik atas Ijma' dan Penolakan Qiyas - Sidanatul Janah (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
The debate regarding the position of Ijma' and Qiyas as sources of Islamic law is generally explained more from a Sunni perspective, so studies are still needed that confirm the basis for limiting Ijma' and rejecting Qiyas in Shi'ite Imami legal epistemology. This article was prepared through a literature study with descriptive-critical analysis of ushul fiqh literature and Islamic legal thought, especially those related to the legal construction of the Shi'ah Imamiyah school of law. The results of the study show that Ijma' in the Shi'ah Imamiyah school of thought does not have the status of an independent proposition, but only has the value of hujjah if it reveals or confirms the opinion of Imam Ma’shum. Meanwhile, Qiyas was firmly rejected because it was seen as not having the legitimacy of the text and had the potential to give rise to legal decisions that relied on conjecture. Instead, Shiite Imamiyah places reason ('aql) as one of the important instruments in legal istinbath, alongside the Qur'an, Sunnah, and Ijma' which are connected to the authority of Imam Ma’shum. This finding confirms that the differences between Sunni and Imami Shia in the use of legal sources are epistemological in nature and have a direct impact on the method of establishing Islamic law.